#TITLE_ALTERNATIVE# - DAFANANTO (NIM 10203014) pembimbing : Dr. Herman, AFFAN
The organic molecule of Disperse red 1 has been known as nonlinear optic material and has abroad potential applications as photonic devices. To obtain a suitable devices, the material should be fabricated in form of films. Furthermore, the additional control on the molecular orientation is required to obtain parallel dipolar agregate which show a large second order nonlinear optic properties. In this research, the thin film was fabricated by E-PVD method. Electric field and surfactant effect was used to obtain parallel dipolar molecular orientation in film. The molecular control mechanism which underlined process of orientation of molecules is modeled by dipole interaction and interaction with electric field. The resulted thin film was characterized by UV-VIS spectroscopy to verified those mechanism.